Morphosyntax of Katcha nominals: a Dynamic Syntax account - Turner, Darryl John (The University of Edinburgh, 2016)
This thesis presents a new description and theoretical analysis of the nominal system of Katcha (Nilo-Saharan, Kadu), spoken in the Nuba Mountains of Sudan. The description and analysis are based on a synthesis of data from several sources, including unpublished archive material and original fieldwork. The study is placed in context with a discussion of the demographic, cultural and political background affecting the Katcha linguistic community, a review of the current state of linguistic research on Katcha and a discussion of the ongoing controversy over the place of the Kadu languages within the language phyla of Africa. The morphosyntactic descriptions first focus on the role of nominals as heads, considering phenomena such as classification, agreement and modification. It is shown that Katcha has a unusual system of gender agreement with three agreement classes based on the concepts of Masculine, Feminine and Plural and that the gender of a noun may change between its singular and plural forms. Surprisingly, these phenomena are both most commonly found in Afro-Asiatic, which is not a phylum to which Kadu has previously been ascribed. The gender changes are shown to be predictable, determined by number-marking affixes. The study then gives a unified analysis of various types of nominal modifiers; relative clauses, possessives, demonstratives and adjectives all display similar morphological properties and this is accounted for by analysing all modfiers as appositional, headed by a demonstrative pronoun. This analysis of modifiers shows them to be related to, though not the same as, the notions of relative markers and construct state found widely in African languages. The role of nominals within sentential argument structure is then considered, with discussion of phenomena such as prepositional phrases, case and verbal valency. From the interaction of prepositions and pronouns, it is tentatively concluded that Katcha has three cases: Nominative, Accusative and Oblique. From the interaction of verbs and nouns, it is demonstrated that the verbal suffixes known as ‘verb extensions’ primarily serve to license the absence of otherwise mandatory core arguments. The second part of the thesis provides a theoretical analysis of the nominal system within the framework of Dynamic Syntax (DS). Two key features of the DS formalism come into play. Firstly, DS construes semantic individuals as terms of the epsilon calculus. Verb extensions are analysed as projecting context-dependent epsilon terms, providing a value for the ‘missing’ argument. Secondly, DS allows information sharing between propositions by means of a ‘LINK’ relation. Prepositional phrases are analysed as projecting a subordinate proposition which shares an argument with the matrix tree. These two formal tools come together in the analysis of nominal modifiers, which are construed as projecting an arbitrarily complex epsilon term LINKed to some term in the matrix tree, directly reflecting their descriptive analysis as appositional nominals. In presenting new data for a little studied language, this thesis adds to our knowledge and understanding of Nuba Mountain languages. In describing and analysing some of the typologically unsual features of Katcha’s nominal system, it challenges some standard assumptions about these constructions and about the genetic affiliation of the Kadu family. And in the theoretical analysis it demonstrates the suitability of Dynamic Syntax to model some of the key insights of the descriptive analysis.
Keywords: Nuba Mountain languages; nominals; modifiers; gender; Dynamic Syntax